Informacje fonetyczno -ortofoniczne w podręczniku Tomasza Karpowicza Kultura języka polskiego . Wymowa , ortografia , interpunkcja. - Nowakowski, Paweł; Wiatrowski, Przemysław (Slavia Occidentalis, 2013)
The aim of the article is to assess the quality of phonetic and orthophonetic knowledge presented in the academic textbook by Tomasz Karpowicz entitled Polish Language Culture. Pronunciation, Spelling and Punctuation, Wydawnictwo Naukowe PWN, Warsaw 2009. An analysis of phonetic and orthophonetic information has identified numerous factual mistakes and gaps, as many pronunciation problems requiring definition of correct standards were disregarded.